Ni(II) complexes with 1,3,2,4-dithiadiphosphetane 2,4-disulfide-based ligands: Structural insights, theoretical studies, and anticancer activities - SAĞLAM, ERTUĞRUL GAZİ (My University, 2022)
The first synthesis of 2,4-bis(3,4-dimethoxyphenyl)-1,3-dithia-2,4-diphosphetane 2,4-disulfide (SAV-A1 reagent) was achieved. Seven oxo-alkyl esters (HLn) were synthesized thereof. Ni(II) complexes ([Ni(Ln)2]) of these ligands were prepared in ethanol. The structures were identified by spectral studies. Ni(II) complexes were unambiguously determined by X-ray crystallography. In addition, the ligands and their Ni(II) complexes were tested on two different human cancer cell lines, including liver and colon. Moreover, density functional theory (DFT) calculations of the Ni(II) complexes were performed, and the molecular docking studies of these compounds with liver cancer protein, PDB ID: 3WZE and colon cancer antigen proteins, ID 2HQ6 were presented to investigate and predict potential interactions.
Keywords: Kimya; İnorganik Kimya; Diğer; Temel Bilimler; Chemistry; Inorganic Chemistry; Other; Natural Sciences; KİMYA, UYGULAMALI; Temel Bilimler (SCI); KİMYA, İNORGANİK VE NÜKLEER; CHEMISTRY, APPLIED; CHEMISTRY; Natural Sciences (SCI); CHEMISTRY, INORGANIC & NUCLEAR; İnorganik kimya; Kimya (çeşitli); Genel Kimya; Proses Kimyası ve Teknolojisi; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Process Chemistry and Technology; Physical Sciences; 2; 4-diorganyl-1; 3; 4-dithiadiphosphetan-2; 4-disulfide; anticancer; density functional theory; dithiophosphonato complexes; perthiophosphonic acid anhydrides; NI-II COMPLEXES; NUCLEAR-MAGNETIC-RESONANCE; COORDINATION POLYMERS; CRYSTAL-STRUCTURE; NMR-SPECTROSCOPY; ANTIBACTERIAL ACTIVITY; INDIVIDUAL GAUGE; SOLID-STATE; ACID; DITHIOPHOSPHONATES; 2,4-diorganyl-1,3,2,4-dithiadiphosphetan-2,4-disulfide; 2; 4-diorganyl-1; 3; 2; 4-dithiadiphosphetan-2; 4-disulfide; anticancer; density functional theory; dithiophosphonato complexes; perthiophosphonic acid anhydrides